Virologic Response to Early Antiretroviral Therapy in HIV-infected Infants: Evaluation After 2 Years of Treatment in the Pediacam Study, Cameroon. Issue 1 (January 2018) - Ateba Ndongo, Francis; Texier, Gaetan; Ida Penda, Calixte; Tejiokem, Mathurin Cyrille; Tetang Ndiang, Suzie; Ndongo, Jean-Audrey; Guemkam, Georgette; Sofeu, Casimir Ledoux; Kfutwah, Anfumbom; Faye, Albert; Msellati, Philippe; Warszawski, Josiane
Abstract : Introduction: Little is known about virologic responses to early antiretroviral therapy (ART) in HIV-infected infants in resource-limited settings. We estimated the probability of achieving viral suppression within 2 years of ART initiation and investigated the factors associated with success. Methods: We analyzed all 190 infants from the Cameroon Pediacam who initiated ART by 12 months of age. The main outcome measure was viral suppression (<1000 copies/mL) on at least 1 occasion; the other outcome measures considered were viral suppression (<400 copies/mL) on at least 1 occasion and confirmed viral suppression (both thresholds) on 2 consecutive occasions. We used competing-risks regression for a time-to-event analysis to estimate the cumulative incidence of outcomes and univariate and multivariate models to identify risk factors. Results: During the first 24 months of ART, 20.0% (38) of the infants died, giving a mortality rate of 11.9 deaths per 100 infant-years (95% confidence interval: 8.1–15.7). The probability of achieving a viral load below 1000 or 400 copies/mL was 80.0% (69.0–81.0) and 78.0% (66.0–79.0), respectively. The probability of virologic suppression (with these 2 thresholds) on 2 consecutive occasions was 67.0% (56.0–70.0) and 60.0% (49.0–64.0), respectively. Virologic success was associated with not having missed any doses of treatment before the visit, but not with socioeconomic and living conditions. Conclusion: Many early treated children failed to achieve virologic suppression, likely due to a combination of adherence difficulties, drug dosing and viral resistance, which highlights the need for routine viral load monitoring. The high infant mortality despite early ART initiation needs to be addressed in sub-Saharan countries. Abstract : Supplemental Digital Content is available in the text.